THE ASSOCIATION OF SOCIODEMOGRAPHIC FACTORS WITH MOTOR SYMPTOMS IN PATIENTS WITH PARKINSONISM - Dyson, Nathaniel Gilbert; Tiksnadi, Amanda (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Motor symptoms in patients with parkinsonism severely impair daily activities. Sociodemographic factors are known to play an important role in various chronic diseases, but their relationship with parkinsonism has not been studied yet. Objective: This study aims to determine the association between sociodemographic factors and motor symptoms among patients with parkinsonism. Methods: This cross-sectional study was conducted at Dr. Cipto Mangunkusumo National Hospital Jakarta by using the MDS Unified Parkinson's Disease Rating Scale (MDS-UPDRS) Part II questionnaire about daily motor symptoms. The target sample in this study were patients with parkinsonism based on a doctor's diagnosis, fluent in Indonesian, and had internet access. Results: A total of 50 respondents were recruited with the most motor symptoms being difficulty dressing (90%), followed by writing, doing hobbies, tremors, and balance (88%). Bivariate analysis found that patients with low education, low income, and married had significantly worse motor symptoms (p<0.05). Multivariate analysis revealed that low education level and married status were significant risk factors, while high income level was a protective factor against poor motor symptoms. Conclusion: Sociodemographic factors were significantly associated with motor symptoms in parkinsonism patients. This study recommends personalized patient management based on the patient's sociodemographic factors.